Viability equation to determine the longevity of fungicide-treated seeds of wheat stored in a conventional warehouse - doi: 10.4025/actasciagron.v33i3.6455 (Acta Scientiarum. Agronomy, 2011)
The objective of this research was to determine the deterioration rate of BRS 208 and CD 104 wheat cultivar seeds, treated with fungicides, by applying the viability equation. Seeds were stored in conventional warehouses in Mauá da Serra and Londrina, in the State of Paraná, Brazil. Four seed lots were divided into four replications, half being treated with Carboxin + Thiran and the other half taken as controls, without treatment, and these were stored for 300 days. The germination data were transformed into probit, and a straight line was adjusted between 0 and 30 days. The treated seed lot of cv. BRS 208 stored in Londrina gave seed deterioration rates varying from 0.8.10-3 to 1.3.10-3, not differing from the values given for the similar lot stored in Mauá da Serra, of 0.9.10-3.The deterioration rates of the treated seed of cv. CD 104 were 1.2.10-3 in Mauá da Serra and 2.0.10-3 in Londrina, which are greater than those values given for untreated seeds of 0.4.10-3 and 0.5.10-3.This model provides an effective approach to predict the untreated and treated seed longevity of wheat for the purpose of managing seeds.